Strontium enhances BMP‐2 mediated bone regeneration in a femoral murine bone defect model. Issue 1 (5th April 2019) - Quade, Mandy; Vater, Corina; Schlootz, Saskia; Bolte, Julia; Langanke, Robert; Bretschneider, Henriette; Gelinsky, Michael; Goodman, Stuart B.; Zwingenberger, Stefan
Abstract: The application of strontium is one option for the clinical treatment of osteoporosis—a disease characterized by reduced bone density and quality—in order to reduce the risk of vertebral and nonvertebral fractures. Unlike other drugs used in osteoporosis therapy, strontium shows a dual effect on bone metabolism by attenuating cellular resorption and simultaneously enhancing new bone tissue formation. Current concerns regarding the systemic application of highly dosed strontium ranelate led to the development of strontium‐modified scaffolds based on mineralized collagen (MCM) capable to release biologically active Sr 2+ ions directly at the fracture site. In this study, we investigated the regenerative potential of these scaffolds. For in vitro investigations, human mesenchymal stromal cells were cultivated on the scaffolds for 21 days (w/ and w/o osteogenic supplements). Biochemical analysis revealed a significant promoting effect on proliferation rate and osteogenic differentiation on strontium‐modified scaffolds. In vivo, scaffolds were implanted in a murine segmental bone defect model—partly additionally functionalized with the osteogenic growth factor bone morphogenetic protein 2 (BMP‐2). After 6 weeks, bridging calluses were obtained in BMP‐2 functionalized scaffolds; the quality of the newly formed bone tissue by means of morphological scores was clearly enhanced in strontium‐modified scaffolds. Histological analysis revealed increased numbers of osteoblasts and blood vessels, decreased numbers of osteoclasts, and significantly enhanced mechanical properties. These results indicate that the combined release of Sr 2+ ions and BMP‐2 from the biomimetic scaffolds is a promising strategy to enhance bone regeneration, especially in patients suffering from osteoporosis. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 108B:174–182, 2020.